A Problem Solving Based Learning Model for Enhancing Students’ Critical Thinking and Creativity Skills in the Digital Era - Danan Wuryanto Pramono; Moh. Yahya Obaid; Bagiya Bagiya; Pariyati Pariyati; Ahmad Faqihudin (Mandalika Institute, 2026)
This study explores the effectiveness of the Problem Solving Based Learning (PSBL) model in enhancing students’ critical thinking and creativity within digital learning environments. A qualitative literature review approach was employed to examine scholarly sources related to PSBL, critical thinking, creativity, and the integration of digital technologies in education. The findings indicate that PSBL promotes higher-order cognitive skills through authentic problem-solving tasks, collaborative learning, and reflective practices. These components encourage students to engage with real-world issues, evaluate information critically, generate innovative solutions, and reflect on their learning processes. Furthermore, the integration of digital tools, including online platforms, simulations, and virtual reality, enriches the problem-solving experience by expanding access to information, facilitating real-time collaboration, and providing immersive learning opportunities. The novelty of this study lies in the development of an integrated conceptual framework that synthesizes problem-solving processes, collaborative learning, reflective practices, and digital technologies into a unified model for fostering both critical thinking and creativity. The study also contributes theoretically by extending constructivist and digital pedagogy perspectives through a comprehensive explanation of the mechanisms linking PSBL implementation to higher-order cognitive and creative outcomes. It is concluded that PSBL, when effectively supported by digital technologies, offers a robust pedagogical framework for preparing students to meet the complex challenges of the 21st century. Future research should investigate the long-term effectiveness of the model across diverse educational contexts and technological settings.